Development of Integrated Approaches to Testing and Assessment (IATA) case studies on developmental neurotoxicity (DNT) risk assessment. (18th June 2021) - ,; Hernández‐Jerez, Antonio; Adriaanse, Paulien; Aldrich, Annette; Berny, Philippe; Coja, Tamara; Duquesne, Sabine; Focks, Andreas; Marinovich, Marina; Millet, Maurice; Pelkonen, Olavi; Pieper, Silvia; et al.
Abstract: The EFSA Panel on Plant Protection Products and their Residues (PPR) has developed, as a self‐task mandate (EFSA‐Q‐2019‐00100), two adverse outcome pathway (AOP)‐informed integrated approach to testing and assessment (IATA) case studies to answer a developmental neurotoxicity (DNT) hazard identification and characterisation problem formulation that could support the regulatory decisions for the pesticide active substances deltamethrin and flufenacet. The IATA were developed to assess the applicability of the DNT in vitro testing battery (IVB), designed to explore fundamental neurodevelopmental processes, in the regulatory risk assessment of pesticides. For this purpose, an evidence‐based‐approach methodology was applied: 1) systematic literature review and critical appraisal of all the evidence i.e. human observational studies, in vivo data from rodent models and new approach methodologies (NAMs, i.e. in vitro studies including high‐throughput testing from IVB and zebrafish studies from the literature) for both case studies; 2) a quantitative uncertainty analysis of all the evidence using expert knowledge elicitation (EKE) and a probabilistic approach; 3) integration of all the evidence using the AOP conceptual framework. This stepwise approach resulted in the postulation of an evidence‐based AOP network for one of the case studies. A probabilistic quantification of the weight of evidence (WoE) using Bayesian network analysis allowed the assessment and the quantification of the uncertainty in the postulated AOP. The approach taken allowed conclusions to be drawn with an acceptable level of certainty in DNT hazard identification and characterisation of deltamethrin and that flufenacet is not a developmental neurotoxicant, supporting the relevance of the mechanistic understanding. The case studies show the applicability of the DNT‐IVB for hazard identification and characterisation and illustrate the usefulness of an AOP‐informed IATA for regulatory decision making. The overall activity led to improved interpretation of human data by providing a plausible mechanistic link to adverse outcomes, which would support their contextualisation in the risk assessment process. This Scientific Opinion allows the PPR Panel to draft several recommendations for the implementation of the AOP‐informed IATA methodology and of the DNT‐IVB in the regulatory risk assessment of pesticides.